2020
DOI: 10.1177/1559325820959563
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Response ofEpimedium gandiflorum’sDifferent Doses to Restore the Antioxidant Potential and Reproductive Hormones in Male Albino Rats

Abstract: Current study was planned to explore the therapeutic response of different doses of hydroethanolic extract of Epimedium grandiflorum leaves in male albino rats. Phytochemical analysis, HPLC and FTIR spectroscopy results revealed the presence of wide range of phenolic compounds and functional groups, respectively. Further, extract not induced significant hemolysis (7.56 ± 1.297%) against PBS (3.65 ± 0.35%) as negative control; while have significant clot lysis (44 ± 5.2%) potential, exhibited DPPH (78.87 ± 5.42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Munir et al also reported an elevated serum testosterone level as a result of orally administrating different doses of the extract of the herb Epimedium gandiflorum. 11 The reports obtained from this study conforms with that of Boepple et al, stating that, an increase in LH and FSH secreted from the anterior pituitary in response to GnRH (secreted from the hypothalamus), results in an increase in the gonadal hormone, testosterone secreted by Leydig cells in testes. 13 There was a significant increase in the mean semen volume after a week of treatment (group B), 3 weeks of treatment (group D) and 6 weeks treatment (group F) when compared to the negative control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Munir et al also reported an elevated serum testosterone level as a result of orally administrating different doses of the extract of the herb Epimedium gandiflorum. 11 The reports obtained from this study conforms with that of Boepple et al, stating that, an increase in LH and FSH secreted from the anterior pituitary in response to GnRH (secreted from the hypothalamus), results in an increase in the gonadal hormone, testosterone secreted by Leydig cells in testes. 13 There was a significant increase in the mean semen volume after a week of treatment (group B), 3 weeks of treatment (group D) and 6 weeks treatment (group F) when compared to the negative control.…”
Section: Discussionsupporting
confidence: 91%
“…10 The reports from this study may also be attributed to the individual herbs (containing phytochemicals) used in the formulation of the Revive capsule; Munir et al conducted a study by assessing the therapeutic response of different doses of Epimedium gandiflorum (an herb present in Revive capsule); they reported that oral administration of different doses of the plant's extract induced an increase in serum LH and FSH levels in albino rats pretreated with carbon-tetrachloride. 11 The mean testosterone level of group F was significantly higher when compared to those of the other groups. There was a non-significant increase in groups B (after one week of treatment) and C (after two weeks of treatment) when compared with the negative control (group A).…”
Section: Discussionmentioning
confidence: 73%
“…Molecular docking is an elaborative method to discover the binding features of different small molecules as drugs against the target proteins [19][20][21]. The natural flora plays a vital role in drug screening and development [22][23][24]. The crude extracts of different medical plants have been reported with biologically active compounds with multiple clinical activities against many diseases [25,26].…”
Section: Discussionmentioning
confidence: 99%
“… 31 Icariin was reported to function as a regulator of adaptive immunity in 1995, 32 and subsequent studies have revealed antihepatotoxic 33 and antioxidant 34 activities as well as the ability to stimulate corticosterone production 35 and promote neurite outgrowth. 36 Icariin has pharmacologic effects on the immune, 37 skeletal 38 and reproductive 39 systems. Over the past few years, an increasing number of studies have focused on the protective effects of icariin in the nervous system diseases.…”
Section: Historymentioning
confidence: 99%